2020
DOI: 10.1093/jcag/gwz047.041
|View full text |Cite
|
Sign up to set email alerts
|

A42 Microbial Metabolism of Dietary Tryptophan Enhances Aryl Hydrocarbon Receptor Activation: Implications for Ibd

Abstract: Background Intestinal immune homeostasis is maintained by the interplay between microbiota and the mucosal immune system. Changes in gut microbiota have been associated with chronic intestinal conditions, such as inflammatory bowel disease (IBD). The aryl hydrocarbon receptor (AhR) is a transcription factor that is activated by dietary and environmental stimuli to control immune responses in the gut and homeostatic mechanisms at mucosal surfaces. In IBD, AhR expression is downregulated. Major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[ 80 ] The recent study showed that dietary Trp treatment enhanced AhR activation capacity and altered fecal microbiota in IBD patients, and that is associated with microbiota‐mediated Trp metabolites indole derivatives. [ 182 ] Based on the above vital roles of Trp and its metabolites in regulating inflammation, Trp could be considered as a potential target for the development of new approaches for controlling IBD.…”
Section: Role Of Trp and Its Metabolites In Inflammatory Bowel Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…[ 80 ] The recent study showed that dietary Trp treatment enhanced AhR activation capacity and altered fecal microbiota in IBD patients, and that is associated with microbiota‐mediated Trp metabolites indole derivatives. [ 182 ] Based on the above vital roles of Trp and its metabolites in regulating inflammation, Trp could be considered as a potential target for the development of new approaches for controlling IBD.…”
Section: Role Of Trp and Its Metabolites In Inflammatory Bowel Diseasementioning
confidence: 99%
“…[181] As well, dietary Trp treatment can enhance AhR activation capacity and alter fecal microbiota in IBD patients by indole derivatives. [182] Along with, tryptamine, IPA, and IAA also act as the high-affinity ligands of AhR and are involved in regulating inflammation in IBD patients by effecting pro/anti-inflammatory cytokines and intestinal microbial composition. [56] Besides GCN2, mTOR, and AhR signal molecule, 5-HT also drives intestinal inflammation in IBD patients through interacting with 5-HTRs.…”
Section: Role Of Trp and Its Metabolites In Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation